Earthquake-response of open ground storey reinforced concrete building retrofitted with and without yield type X shaped metallic elasto-plastic damper - Madheswaran, C.K.; Gopalakrishnan, N.; Prakashvel, J.; Kumar, K. Sathish (Journal of Structural Engineering, 2024)
A three-storey half scale Reinforced Concrete (RC) building frame model, fitted with yielding type X-shaped metallic elasto-plastic damper at the ground floor level, is designed and fabricated to study its seismic response characteristics. Experimental studies are carried out using the 4m × 4m tri-axial shake-table facility to evaluate the seismic response of a retrofitted RC frame building with Open Ground Storey (OGS) structure using yielding type X-shaped metallic elasto-plastic dampers (also called as Added Damping and Stiffness-ADAS elements) and repairing ground storey columns using Geopolymer concrete composites. In general, earthquake loading introduces large displacements in an OGS structure, and under such large displacements, a yielding type elasto-plastic device made of X-shaped metallic dampers is expected to perform better. The supporting steel frame of ADAS element is of chevron type, serially contributing stiffness to the ADAS element. Free vibration tests on RC frame building without and with yielding type X-shaped metallic damper are carried out. The natural frequencies and mode shapes of model without and with yielding type X-shaped metallic elasto-plastic damper are obtained. The reinforced concrete building is subjected to earthquake excitations. Further, seismic responses of the structure with metallic damper are evaluated with different earthquake excitations.